ANTIOXIDANT AND ANTIBACTERIAL ACTIVITIES OF ENDOPHYTIC FUNGI EXTRACTS FROM THE FLOWER OF PURUN TIKUS (Eleocharis dulcis (Burm.f.) Trin. Ex Hensch.) - Kurratul Aini; Syarifah; Siti Elisya Balkia; Sonia Wiji Febrianti; Elizah Febrianti (BRIN Publishing (Penerbit BRIN), 2026)
Purun Tikus (Eleocharis dulcis (Burm.f.) Trin. Ex Hensch.) is a wetland plant native to Southeast Asia known to contain various bioactive secondary metabolites. However, studies on endophytic fungi associated with the flowers of this plant remain limited, even though endophytes are often capable of producing compounds similar to or even more potent than those of their host plants. This study aimed to identify and evaluate the antioxidant and antibacterial activities of endophytic fungi isolated from the flowers of E. dulcis. Isolation was carried out using surface sterilization and cultivation on Potato Dextrose Agar (PDA), followed by identification based on macroscopic and microscopic characteristics. Three isolates were successfully obtained: EDF1 (Neopestalotiopsis sp.), EDF2 (Lasiodiplodia theobromae), and EDF3 (Rhizopus sp.). Secondary metabolites were extracted using ethyl acetate, while antioxidant and antibacterial activities were evaluated using the DPPH method and agar disc diffusion method, respectively, against Salmonella typhi, Escherichia coli, Staphylococcus aureus, and Bacillus subtilis. The results showed that each isolate exhibited different levels of bioactivity. Among them, EDF2 (L. theobromae) demonstrated the highest activity, with an IC₅₀ value of 19.149 µg/mL (categorized as very strong) and antibacterial inhibition exceeding 80% against all tested bacteria. These findings indicate that L. theobromae has strong potential as a natural source of bioactive compounds that can be further developed as candidates for phytopharmaceuticals, antimicrobial agents, and natural antioxidants through subsequent in vivo studies.